2015
DOI: 10.1080/02701367.2014.995019
|View full text |Cite
|
Sign up to set email alerts
|

Top 10 Research Questions Related to Physical Activity and Bone Health in Children and Adolescents

Abstract: Evidence strongly supports a positive, causal effect of physical activity on bone strength and suggests long-term benefits of childhood physical activity to the prevention of osteoporosis. The contribution of healthy bone development in youth is likely to be as important to fracture prevention as the amount of late adulthood bone loss. Families, schools (particularly physical education), and communities are key settings for health promotion focused on bone-enhancing physical activity. However, little research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Physical activity (PA) is an important modifiable factor in the improvement of children's cardiometabolic (Boddy et al 2014), musculoskeletal (Janz, Thomas, Ford & Williams, 2015), and psychological health (Ahn & Fedewa, 2011), and supports cognitive (Carson et al 2015) and fundamental movement skill development (Lubans, Morgan, Cliff, Barnett, & Okely, 2010). The UK Government recommends that children should accumulate at least one hour of moderate to vigorous intensity PA (MVPA) each day, and reduce time spent in sedentary behaviours (Department of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) is an important modifiable factor in the improvement of children's cardiometabolic (Boddy et al 2014), musculoskeletal (Janz, Thomas, Ford & Williams, 2015), and psychological health (Ahn & Fedewa, 2011), and supports cognitive (Carson et al 2015) and fundamental movement skill development (Lubans, Morgan, Cliff, Barnett, & Okely, 2010). The UK Government recommends that children should accumulate at least one hour of moderate to vigorous intensity PA (MVPA) each day, and reduce time spent in sedentary behaviours (Department of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Through the work of the NOF-ASN scientific statement on development of peak bone mass coming out later this year, 2015, and in considering the top 10 research questions relating physical activity and bone health in children and adolescents (Janz et al, 2015), it became clear that there are obvious differences in how the disciplines of nutrition and physical activity address questions related to bone and other issues. Nutrition uses a reductionist approach with much more data on the effects of individual nutrients than for global diet patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The article "Top 10 Research Questions Related to Physical Activity and Bone Health in Children and Adolescents" by Janz, Thomas, Ford, and Williams (2015) contributed to my supposition that there are many parallels between two of the most important fields-namely, physical activity and nutrition science, which study lifestyle choices that influence bone health. At a superficial level, this observation has been obvious for some time.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Because osteopenia is so much more common than osteoporosis, the majority of fractures occur in the population of patients with osteopenia12 ) . There is a positive effect of physical activity on bone strength and on preventing osteoporosis13 ) . Strophe et al14 ) showed that physical activity during growth increases bone mass and strength with persistent benefits15 ) .…”
Section: Introductionmentioning
confidence: 99%